Visual Teams: Graphic Tools for Commitment, Innovation, and High Performance - Sibbet, David (Wiley, 2011)
Graphic tools and visual solutions for team building and developmentVisual Teamsuses visual tools and methods to help teams—both face-to-face and virtual—reach high performance in today's work environment. As teams become more and more global and distributed, visualization provides an important channel of communication—one that opens up the group's mind to improving work systems and processes by understanding relationships, interconnections, and big picture contexts.Visual Teamsshares best practices and uses visualization as a power tool for process improvement by providing teams with a common language for high performance. The book:Explores how any kind of team can draw on the principles and practices of creative design teams in the software, architectural, engineering, and information design professionsIntroduces the Drexler/Sibbet Team Performancetrade; Model and related tools—a system used throughout companies such as Nike, Genentech, Becton Dickinson, Chevron, and othersVisual Teamspresents a comprehensive framework, best practices, and unique visual tools for becoming an innovative, high-performance team.